1998
DOI: 10.1097/00005537-199808000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Neck dissection with simultaneous carotid endarterectomy

Abstract: Severe carotid stenosis that requires revascularization may have endarterectomy performed simultaneously with treatment of head and neck primary with no increase in morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 11 publications
0
23
1
2
Order By: Relevance
“…They reported the risk of stroke during neck dissection to be 3.2% and 4.8%. 7,9 The implications of these results are significant because they suggest a potential need for preoperative screening and/or intervention for carotid artery pathology. 10 -15 We therefore initiated this study to verify the above results by determining the incidence of perioperative stroke after neck dissection for head and neck cancer in a large Canadian city.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They reported the risk of stroke during neck dissection to be 3.2% and 4.8%. 7,9 The implications of these results are significant because they suggest a potential need for preoperative screening and/or intervention for carotid artery pathology. 10 -15 We therefore initiated this study to verify the above results by determining the incidence of perioperative stroke after neck dissection for head and neck cancer in a large Canadian city.…”
mentioning
confidence: 99%
“…7 During carotid endarterectomy, the risk has been reported to be between 0.9% and 3.6%. 7,8 After a critical review of the literature, only 2 studies were found that addressed the incidence of perioperative stroke during head and neck surgery. They reported the risk of stroke during neck dissection to be 3.2% and 4.8%.…”
mentioning
confidence: 99%
“…In addition, the carotid artery is frequently retracted, which may dislodge a thrombus or plaque (10). The incidence of perioperative stroke during the performance of non-neck and head surgery is 0.08-0.2% (11). There are a limited number of reports regarding the incidence of perioperative stroke in patients who undergo neck dissection.…”
Section: Discussionmentioning
confidence: 99%
“…Deux cas particuliers mé ritent d'être cité s, la chirurgie ORL et la chirurgie obsté tricale : en chirurgie ORL, deux travaux mis en exergue comme exemple d'une particularité lié e à la chirurgie oncologique ORL, trouvent une fré quence trè s é levé e de 3,2 et 4,8 % [138,139], ce qui n'est pas confirmé par une sé rie plus ré cente : 0,2 % (intervalle de confiance 0,01-1,12) [140]. Ces travaux sont critiquables [141].…”
Section: Populations Particulie`resunclassified